Examining the language skills of children with ADHD following a play-based intervention - Docking, K.; Munro, N.; Cordier, Reinie; Ellis, P. (Sage Publications, 2013)
Communication and play skills are important aspects of development yet are largely uncharted inchildren with attention deficit hyperactivity disorder (ADHD). This exploratory study examinedwhether changes in pragmatic skills and problem-solving skills were observed in children withADHD pre- and post-participation in a play-based intervention conducted by occupationaltherapists and speech-language pathologists. The study also investigated whether the presence oflanguage difficulties affected the children’s play outcomes. Fourteen children with ADHD (5;0–10;7 years) participated in a 7-week, pilot intervention to address play and social skill deficits.Pre- and post-intervention testing included: (a) the assessment of play and problem-solving skillsvia standardized testing, and (b) pragmatic skills via parent report. The children’s language skillswere also screened and compared with their play scores. Play skills significantly improved postintervention.No significant differences were observed for pragmatic skills while prediction skills,an aspect of problem-solving, significantly improved pre- and post-play-based intervention. Fiftypercent of children failed the language screener, yet separate paired t-tests identified significantplay improvements irrespective of the presence or absence of language difficulty. Two independentt-tests revealed significant differences in play scores between these groups at pre- but not postintervention.While play and predicting skills significantly improved post-play-based intervention, otheraspects of problem-solving and pragmatics did not. Reasons for the lack of change in these areasare discussed. The presence of language difficulties did not appear to affect the play outcomesof children with ADHD following a play-based intervention. A larger scale experimental trialinvestigating the play and language skills of children with ADHD is warranted, as is futurecollaborative research between occupational therapists and speech-language pathologists in the assessment and management of children with ADHD.